2006
DOI: 10.4049/jimmunol.177.1.712
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of α Fetoprotein (AFP)-Specific T Cell Responses in Subjects with AFP-Positive Hepatocellular Cancer

Abstract: We identified a series of immunodominant and subdominant epitopes from α fetoprotein (AFP), restricted by HLA-A*0201, which are recognized by the human T cell repertoire. The four immunodominant epitopes have been tested for immunogenicity in vivo, in HLA-A*0201+AFP+ advanced stage hepatocellular cancer (HCC) patients, and have activated and expanded AFP-specific IFN-γ-producing T cells in these patients, despite high serum levels of this self Ag. Here, we have examined the frequency, function, and avidity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 13 publications
6
52
0
Order By: Relevance
“…Specific CD4 ϩ T cell responses were of a low frequency as evidenced by detection after in vitro expansion but not directly ex vivo. Similarly as other groups, we have detected AFP-specific CD8 ϩ T cell responses ex vivo in HCC (15,16).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Specific CD4 ϩ T cell responses were of a low frequency as evidenced by detection after in vitro expansion but not directly ex vivo. Similarly as other groups, we have detected AFP-specific CD8 ϩ T cell responses ex vivo in HCC (15,16).…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that the rationale behind an effective epitope-based therapeutic vaccine is to enhance both tumor-specific CD8 ϩ and CD4 ϩ T cell responses, thus controlling tumor growth (11). A number of studies have identified AFP-specific CTLs and demonstrated their presence in patients with hepatocellular carcinoma (12)(13)(14)(15)(16). CD4 ϩ helper T cells are also important in generating potent anticancer immunity, as they can prime and expand CD8 ϩ memory T cells (17) or induce tumor regression in the absence of CD8 ϩ T cells, including MHC class II-negative or MHC class II-positive tumors (18,19).…”
Section: Unmasking Of ␣-Fetoprotein-specific Cd4 ؉ T Cell Responses Imentioning
confidence: 99%
“…For example, several human leukocyte antigen (HLA) class I-restricted AFP-specific epitopes have been identified by different approaches and shown to be present in HCC patients. [6][7][8][9] Indeed, in a recent comprehensive analysis using overlapping AFP peptides, we have shown that the majority of patients with HCC showed AFP-specific CD8þ T-cell responses directed against previously unreported epitopes and that these responses were primarily detectable in the tumor tissue. 5 Importantly, however, we did not find an association between the presence of CD8þ T-cell responses to AFP and the progression or prognosis of HCC, 5 suggesting a failure of the tumor-specific CD8þ T cells to control tumor growth.…”
mentioning
confidence: 99%
“…For example, several human leukocyte antigen (HLA) class I-restricted AFP-specific epitopes have been identified by different approaches and shown to be present in HCC patients. [6][7][8][9] Indeed, in a recent comprehensive analysis using overlapping AFP peptides, we have shown that the majority of patients with HCC showed AFP-specific CD8þ T-cell responses …”
mentioning
confidence: 99%
“…The expression of Alpha Fetoprotein (AFP), which normally stops after birth, is found in up to 80% of HCC. AFP-specific CD8+ T-cells have been shown to produce detectable, circulating interferon-gamma in the peripheral blood of HCC patients [7]. Glypican-3 (GPC-3) is another fetal oncoprotein found in over half of HCC, but not present on normal liver tissue.…”
Section: The Anti-tumor Role For the Adaptive Immune Systemmentioning
confidence: 99%